Speech by the Honourable Chief Minister Penang at the Investiture Ceremony on the Occasion of his excellency the Governors Birthdays on 16th July 1976. - Lim, Chong Eu (1976)
It is my pleasant duty to convey to Your Excellency and to Yang Mulia Toh Puan Datin Saadiah the best wishes and heartiest congratulation of the people of Penang on this happy occasion of Your Excellency’s second Official Birthday.